Mixed convection boundary layer flow over a solid sphere in Al2O3-Ag/water hybrid nanofluid with viscous dissipation effects - Elfiano, Eddy; Nik Mohd Izual, Nik Ibrahim; Muhammad Khairul Anuar, Mohamed (Semarak Ilmu Publishing, 2024)
The current study aims to investigate how heat transfer and skin friction develop by modifications in the fundamental advantages of fluids in the presence of mixed convection boundary layer flow over on a sphere in hybrid nanofluids. The numerical solutions for the reduced Nusselt number, local skin friction coefficient temperature profile, and velocity profiles are discovered and clearly presented. The Eckert number, the mixed convection parameter λ, and the nanoparticle volume fraction are all investigated and described. It is found that increasing the volume percentage of nanomaterial in nanofluid enhanced the value of the skin friction coefficient. The low density of nano oxides in hybrid nanofluids, such as alumina, also contributes to reduced friction between fluid and body surface. The findings of a computational investigation demonstrate that the use of a hybrid nanofluid, composed of nanometal and nano-oxide in the form of , has the potential to decrease skin friction while maintaining heat transfer characteristics comparable to that of Ag/water nanofluid. The findings in this publication are new and will be useful to boundary layer flow researchers. It can also be applied as a guideline for experimental investigations with the goal of reducing the cost of operation